Zakes Mda's Non-Human Characters in the Economy of Indigenous Knowledge Systems. Issue 1 (2nd January 2017) - Sewlall, Harry
Abstract : Through the juxtaposition of the real and the unreal, Zakes Mda's novels attest to an investment in indigenous knowledge systems (IKS) which are imbricated in local epistemologies, iconographies and cosmologies. A significant part of Mda's fictional landscape features non-human characters interacting with humans in a manner that defies logic, but is consonant with the writer's worldview on the human/animal connection. This article traces the various interfaces of the human/animal symbiosis which could be located within the ambit of local cultural knowledge formation or, stated differently, within the economy of IKS in the southern African context.